PERAN ARBITRASE ICSID DALAM KERANGKA PENANAMAN MODAL DI INDONESIA - Setiady, Tri (Universitas Wiralodra, 2018)
At present many foreign investment contracts are made by the State subdivisions and State companies on one side with foreign private companies on the other. For countries that want to carry out a lot of business contracts in the field of foreign investment, which of course must provide stimulating incentives for investment, including the provision of supervision of foreign companies, because foreign investment means getting knowledge, experience, technical and managerial fields. The main considerations of foreign investment to carry out business contracts are basically their market expansion, besides the low production costs due to relatively cheaper labor costs, tax-free facilities (tax holidays) and other facilities free of charge by the capital receiving countries ( host states).